Planting & Cultivating native Cactus for catle feed and wildlife utilization in South Texas - Hamilton, J. R. (Journal of the Professional Association for Cactus Development, 1992)
1. Brief history of how and why I became interested in prickly pear. 2. 14 desirable plant characteristics of prickly pear, and 3. Planting methods, maintenance and utilization of prickly pear.